Effects of different initial speeds on subsequent glide and underwater undulatory swimming - Yamakawa, K. K.; Nishiwaki, R.; Takeda, T. (Sports Biomechanics, 2025)
This study aimed to investigate the effect of different initial speeds on the performance during underwater undulatory swimming (UUS). The study included 13 female swimmers. Each participant was asked to perform a 15-m maximum UUS, starting with four different push-off speeds. The experiment was recorded using three underwater cameras; subsequently, a two-dimensional motion analysis was conducted. Statistical parametric mapping (SPM) was employed to identify the position where the UUS velocity stabilised. The findings revealed a significant difference in the average swimming velocities during the first cycle of UUS, which was attributed to the variation in initial speed (p < 0.05) while there is no significant difference in the middle and final cycles. The results of SPM analysis suggested that differences in UUS velocity became negligible after approximately 6-m position from the pool wall, regardless of variations in push-off velocity. Furthermore, it was confirmed that swimmers can reach their maximum achievable UUS velocity at approximately 5-m position, even if they fail to execute an effective push-off from the wall. These findings offer valuable insights for future UUS studies, specifically in choosing suitable cycles for analysis.